Chimerism as an important marker in post-transplant monitoring chimerism monitoring - Cechova, Hana; Leontovycova, Monika; Pavlatova, Lucie (HLA, 2018)
Cell chimerism determination is important for the monitoring of engraftment dynamics and for relapse prediction. Our cohort of 474 patients was divided into two groups according to the determination methods used over time, and by their chimerism status. A significant difference in survival was observed between mixed vs complete chimerism (P < 0.0001 vs P < 0.0002) in both patient groups, and also vs microchimerism (P = 0.0201) in the second group. Detection of mixed chimerism is thus a high-risk factor, and microchimerism is potentially a risk factor in the post-transplantation course. Methods with a high sensitivity for monitoring cell chimerism significantly improve the assessment of patients post-transplant, and they enable the identification of patients with high relapse risk. Supported by MH CZ-DRO (00023736, UHKT).
Keywords: tandemové repetitivní sekvence; dospělí; rejekce štěpu; Genetic Testing; Recurrence; Graft Rejection; Myeloablative Agonists; Adult; Immune Tolerance; Adolescent; homologní transplantace; lidé; Hematopoietic Stem Cell Transplantation; Survival Analysis; transplantace hematopoetických kmenových buněk; příprava pacienta k transplantaci; recidiva; transplantační chiméra; Aged, 80 and over; Tandem Repeat Sequences; Transplantation Conditioning; real-time polymerase chain reaction; chimerism; hematopoietic stem cell transplantation; kohortové studie; Middle Aged; Risk Factors; Cohort Studies; hematologické nádory; Aged; Hematologic Neoplasms; mladiství; nemoc štěpu proti hostiteli; short tandem repeats; Graft Survival; rizikové faktory; genetické testování; Transplantation, Homologous; analýza přežití; lidé středního věku; senioři nad 80 let; imunologická tolerance; senioři; myeloablativní agonisté; Transplantation Chimera; testování histokompatibility; Histocompatibility Testing; přežívání štěpu; kvantitativní polymerázová řetězová reakce; Graft vs Host Disease; Real-Time Polymerase Chain Reaction; Humans